Cor triatriatum sinister with left anomalous pulmonary venous return to innominate vein - Jaschinski, Christoph; Uzdenov, Murat; Loukanov, Tsvetomir (Cardiology in the young, 2019)
Cor triatriatum sinister is a rare congenital abnormality, with varying signs and symptoms related to the anatomic features and the components of the accompanying cardiac abnormalities. We present a 3-year-old girl who underwent successful simultaneous operation with complete loss of the membrane and ligation of vertical vein by anomalous venous return. The principles for surgical management of cor triatriatum can be summarised as radical resection of the membrane and correction of other intracardiac anomalies.